2018
DOI: 10.1111/1756-185x.13363
|View full text |Cite
|
Sign up to set email alerts
|

Disease severity and economic burden in Japanese patients with systemic lupus erythematosus: A retrospective, observational study

Abstract: This descriptive study provides information on the economic burden and clinical characteristics of Japanese patients with SLE based on claims data; high levels of HRU and direct medical costs were exhibited, particularly in patients with moderate or severe disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 34 publications
4
42
0
3
Order By: Relevance
“…of SLE treatment may not be optimal for patients with SLE to prevent flares or reduce detrimental effects. HRU in this study was similar to the results reported by Tanaka et al 14 in a retrospective, observational cohort study conducted using claims data of Japanese patients who were diagnosed with SLE between April 2010 and March 2012. These patients were followed-up for 3 years and data on HRU and costs were analyzed.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…of SLE treatment may not be optimal for patients with SLE to prevent flares or reduce detrimental effects. HRU in this study was similar to the results reported by Tanaka et al 14 in a retrospective, observational cohort study conducted using claims data of Japanese patients who were diagnosed with SLE between April 2010 and March 2012. These patients were followed-up for 3 years and data on HRU and costs were analyzed.…”
Section: Discussionsupporting
confidence: 90%
“…The meagre number of drug classes observed could be explained by the stringent treatment algorithm that defined the LoT in this study as well as by the presence of a standard treatment algorithm for the clinical management of SLE 12,13 . Our treatment pattern assessment was comparable to a previous Japanese study 14 as well with reports from other countries 37,38 . Utilization of antimalarials (e.g.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations